(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article highlights the importance of transportation infrastructure in the phased development of a country's economy, with a focus on the railway transport system. The article emphasizes the crucial role of the transportation sector in connecting different regions of the country and satisfying the transportation needs of the population. The article also discusses the prospects for the development of freight transportation along international transport corridors, which are recognized as a priority for future international relations. The article emphasizes the importance of digital technologies in ensuring high-quality reform of the economy and public life sectors. The article highlights the efforts by the government of Uzbekistan to adopt fundamental documents that lay the normative and legal foundation for further digital reforms. The article also emphasizes the importance of expanding transit corridors to provide access to prospective international markets for the Republic's exported products. The article highlights the increase in investment activity to ensure the sustainable functioning of the entire transportation system. Finally, the article discusses the tasks set to transform the organization and management system of transportation to meet the growing demand for transportation services from the economy and the population. The article further discusses the tasks set to transform the organization and management system of transportation in Uzbekistan. These tasks include improving the level of service, implementing modern information technology, developing the logistics system, and increasing the efficiency and competitiveness of transportation services. The article emphasizes the importance of implementing a comprehensive approach to the development of transportation, taking into account the integration of various modes of transport and the development of intermodal transportation. The article also highlights the need to increase the level of professionalism and qualifications of personnel in the transportation industry.